The ABC of the blood-brain barrier - regulation of drug efflux pumps - Mahringer, Anne; Ott, Melanie; Reimold, Isolde; Reichel, Valeska; Fricker, Gert (Current pharmaceutical design, 2011)
According to the World Health Organization Central nervous system disorders are the major medical challenge of the 21st Century, yet treatments for many CNS disorders are either inadequate or absent. One reason is the existence of the blood-brain barrier, which strictly limits the access of substances to the brain. A key element of the barrier function is the expression of ABC export proteins in the luminal membrane of brain microvessel endothelial cells. Understanding the signaling cascades and the response to endogenous and exogenous stimuli, which lead to altered expression or function of the transporters as well as subsequent modulation of the transporters, may offer novel strategies to overcome the barrier and to improve drug delivery to the brain. This review gives a short overview about structure of the key elements of the blood-brain barrier with emphasis on ABC transporters. An insight into regulation of function and expression of these transport proteins is given and the involvement of these transporters in CNS diseases is discussed.